Metallothionein Gene Expression in Peripheral Blood Lymphocytes as Biomakers of Cadmium Expose Among Male Die Casting Workers in Bangi Malaysia - Ooi, Keok Loo (2010)
Introduction: Die casting is the process of forcing and shaping molten metal usually non ferrous under high pressure into mold cavities which probably emits cadmium (Cd). Cd causes Metallothionein (MT) gene expression. Quantitative reverse transcriptase polymerase chain reaction (RT-PCR) is applicable as a biomarker of Cd exposure. Objective: Objective of this study is to determine the relationship between urinary and blood concentrations of Cd with MT gene expression in peripheral blood lymphocytes among die casting male workers in non ferrous metal industry in Bangi, Selangor. Methodology: A cross sectional study was carry out on 61 respondents who performed task in the administrative division considered as comparative group. Questionnaires were administered to obtain the sociodemography information of respondents. Early shift of minimum 15 ml urine sample was taken from respondents to determine urine cadmium (UCd) concentration using Graphite Furnace Anatomic Absorption Spectrometry (GFAAS). 10ml of blood sample was taken to determine the blood cadmium (BCd) concerntration using GFAAS and MT gene expression level using RT-PCR. Results: The mean±SD of UCd level was 0.037±0.047µg/g creatinine for exposed group and 0.025±0.031 µg/g creatinine for creative group and the difference was not statically significant (Z=1.369, p=0.863). The mean±SD for BCd concerntration was 0.729±0.11 µg/dL for exposed group and 0.323±0.156 µg/dL for comparative group and the difference were statistically significant (t=9.95, p=0.001). The mean±SD MT basal expression was 1.91±0.28 for exposed group and the difference were statistical significant (t=2.391, p=0.02). The mean±SD MT induction expression was 2.62±0.54 for exposed group and 2.11±0.36 for comparative group and the difference was statically significant (t=3.56, p=0.001). The relationship between MT basal expression and BCd in exposed group showed a significant moderate positive correlation between the two variables (r=0.167, p=0.035). Both MT basal expression showed no significant relationship with UCd in exposed group with r=0.09, p=0.067 and r=0.199, p=0.763 respectively. Conclusion: There was a significant correlation between BCd level and MT gene expression. BCd and MT basal expression in appears to be a strong biomarkers for Cd recent expose